Possibility unleashed : pathbreaking lessons for making change happen in your organization and beyond - Harrison, Marc (CEO of healthcare) (McGraw Hill, 2023)
"From the visionary leader of one of America's most innovative healthcare systems comes a game-changing guide that will help you face your fears, transcend discord and polarization, and drive positive systemic change"--